2014
DOI: 10.2967/jnumed.113.129007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 18F-FET PET and Perfusion-Weighted MR Imaging: A PET/MR Imaging Hybrid Study in Patients with Brain Tumors

Abstract: PET using O-(2-18 F-fluoroethyl)-L-tyrosine ( 18 F-FET) provides important diagnostic information in addition to that from conventional MR imaging on tumor extent and activity of cerebral gliomas. Recent studies suggest that perfusion-weighted MR imaging (PWI), especially maps of regional cerebral blood volume (rCBV), may provide similar diagnostic information. In this study, we directly compared 18 F-FET PET and PWI in patients with brain tumors. Methods: Fifty-six patients with gliomas were investigated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 32 publications
6
81
0
5
Order By: Relevance
“…3) glucose metabolism. Similarly, previous studies have shown high 18 F-FET uptake in gliomas with low cerebral blood flow or blood volume (29,30). Therefore, it is unlikely that increased 18 F-FET uptake during seizure activity is caused by hyperperfusion to a major extent.…”
Section: Discussionmentioning
confidence: 51%
“…3) glucose metabolism. Similarly, previous studies have shown high 18 F-FET uptake in gliomas with low cerebral blood flow or blood volume (29,30). Therefore, it is unlikely that increased 18 F-FET uptake during seizure activity is caused by hyperperfusion to a major extent.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, in a study of initial diagnosis of 56 gliomas, 24 of which were glioblastomas, 18 F-FET showed considerably higher TBRmax and larger tumor volumes when compared to regional cerebral blood volume maps derived from perfusion-weighted MR imaging (53). In addition, postoperative 18 F-FET PET has been shown to reveal residual tumor with higher sensitivity than MRI as well as show larger tumor volumes (54).…”
Section: Delineation Of Glioma Extentmentioning
confidence: 97%
“…From the researcher's point of view, this technology provides the optimal requirements for comparative imaging studies using amino acid PET and advanced MRI, ideally with histological confirmation of imaging findings by stereotactic biopsy. However, the problem of MRI-based attenuation correction is currently not fully solved [24] and the clinical value of adding advanced MRI sequences in multiparametric imaging setting has to be confirmed in further studies [25,26].…”
Section: Newer Indications and Recent Developmentsmentioning
confidence: 99%